Optimal asset allocation with Markowitz portfolio selection model in South Africa. - Petje, George Matsoku (My University, 2016)
The main purpose of this study is to construct and determine the performance of the optimal asset allocation portfolio in South Africa by applying Markowitz portfolio optimization model. To further test whether the optimal asset allocations provide superior returns to risk compared to active multi-asset management. A portfolio is constructed using South African equities, bonds and cash, as well as global equities, global bonds and gold. The Markowitz portfolio optimization model formulates an efficient set, selects portfolio having excess return to standard deviation ratio, while satisfying several constraints to construct the efficient frontier. The yearly weightings are constructed starting from 1998 until 2015, and backtested to determine performance. The Markowitz Portfolio selection efficient frontier and portfolios were developed using the following four strategies: the optimum mean-variance portfolio, a portfolio targeting a return of inflation plus 3 percent, a portfolio targeting a return of inflation plus 4 percent, and a portfolio targeting a return of inflation plus 5 percent. The research found, weightings of the optimum mean-variance portfolio averaged 4.5 percent in SA equities, 5.7 percent in SA bonds, 83.7 percent in SA cash, 1.5 percent in global equities, 1.8 percent in global bonds and 2.9 percent in gold. The optimisations done, show that the optimum mean-variance portfolio underperformed on a return basis but performed exceptionally on a sharpe ratio measure. The inflation targeting strategies outperformed the average South African balanced fund, but underperformed the equally weighted and generic portfolios. The Markowitz strategies does not outperform consistently over multiple periods, as indicated by the short to medium term underperformance to the average South African balanced fund. The results of the optimal portfolios show that the Markowitz optimal portfolio can be used as an investment strategy and as a benchmark to measure against active asset allocation performance. Keywords - Return, Standard Deviation, Sharpe Ratio, Efficient Frontier, Optimum Portfolio, Markowitz Model, Asset Allocation.
MBA Thesis
Keywords: Asset allocation,Finance -- Mathematical models,Mathematical optimization,Investments ,Portfolio management,Portfolio management